2013
DOI: 10.4018/jthi.2013040102
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Engage in Electronic Societies via Facebook in the Arab World

Abstract: The purpose of this study is to develop and validate a comprehensive framework to elucidate the relationship between members’ motivations, attitudes, behavior, and usage patterns of Social Networking Sites (SNSs) as a platform of Electronic Societies (e-societies) focusing on Facebook social networking platform. A questionnaire survey method was used to collect data. The sample included Facebook users from six Arab countries. Structural Equation Modeling (SEM), using EQS, was conducted to analyze the data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…In the context of consumer acceptance, hedonic motivation has been found as a determining factor influencing behavior intention to accept, adopt, and use technology (Venkatesh et al, 2012;Childers et al, 2001). Furthermore, e-banking services technology applications have special features that can be used for hedonic motivations, providing opportunity to analyze a user's motivation from different dimensions (Wang et al, 2009;Yaseen and Al Omoush, 2013). Actually, many researchers suggested that hedonic motivations were conceptualized as perceived enjoyment (Yaseen and Al Omoush, 2013;Moon and Kim, 2001;Heijden, 2004).…”
Section: Hedonic Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of consumer acceptance, hedonic motivation has been found as a determining factor influencing behavior intention to accept, adopt, and use technology (Venkatesh et al, 2012;Childers et al, 2001). Furthermore, e-banking services technology applications have special features that can be used for hedonic motivations, providing opportunity to analyze a user's motivation from different dimensions (Wang et al, 2009;Yaseen and Al Omoush, 2013). Actually, many researchers suggested that hedonic motivations were conceptualized as perceived enjoyment (Yaseen and Al Omoush, 2013;Moon and Kim, 2001;Heijden, 2004).…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…Furthermore, e-banking services technology applications have special features that can be used for hedonic motivations, providing opportunity to analyze a user's motivation from different dimensions (Wang et al, 2009;Yaseen and Al Omoush, 2013). Actually, many researchers suggested that hedonic motivations were conceptualized as perceived enjoyment (Yaseen and Al Omoush, 2013;Moon and Kim, 2001;Heijden, 2004). Hence, the following hypothesis is formulated:…”
Section: Hedonic Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…"Collective intelligence increases the capacity for effective action in pursuit of common aims and finding emergent and sustainable solutions to the complex problems." [3] The internal capacities of a corporation have perhaps reached its limit, and a new source of competitiveness is desperately needed to develop sustainable management practices. However, research on identifying cause-and-effect relationships associated with CI is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…"Collective intelligence increases the capacity for effective action in pursuit of common aims and finding emergent and sustainable solutions to the complex problems" [3].…”
Section: Introductionmentioning
confidence: 99%